2014
DOI: 10.1111/tpj.12638
|View full text |Cite
|
Sign up to set email alerts
|

The BSD2 ortholog in Chlamydomonas reinhardtii is a polysome‐associated chaperone that co‐migrates on sucrose gradients with the rbcL transcript encoding the Rubisco large subunit

Abstract: SUMMARYThe expression of the CO 2 -fixation enzyme ribulose-bisphosphate carboxylase/oxygenase (Rubisco), which is affected by light, involves the cysteine-rich protein bundle-sheath defective-2 (BSD2) that was originally identified in maize bundle-sheath cells. We identified the BSD2 ortholog in Chlamydomonas reinhardtii as a small protein (17 kDa) localized to the chloroplast. The algal BSD2-ortholog contains four CXXCXGXG DnaJlike elements, but lacks the other conserved domains of DnaJ. BSD2 co-migrated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 44 publications
(74 reference statements)
2
38
0
1
Order By: Relevance
“…Subsequent work in maize showed that BSD2 likely interacts with nascent LS and/or newly imported small subunit as well as other assembly factors (RAF1 and RAF2) to assemble the Rubisco holoenzyme (Feiz et al, 2012(Feiz et al, , 2014. More limited data are consistent with analogous roles in Nicotiana benthamiana (Wostrikoff and Stern, 2007) and Chlamydomonas reinhardtii (Doron et al, 2014).…”
supporting
confidence: 48%
“…Subsequent work in maize showed that BSD2 likely interacts with nascent LS and/or newly imported small subunit as well as other assembly factors (RAF1 and RAF2) to assemble the Rubisco holoenzyme (Feiz et al, 2012(Feiz et al, , 2014. More limited data are consistent with analogous roles in Nicotiana benthamiana (Wostrikoff and Stern, 2007) and Chlamydomonas reinhardtii (Doron et al, 2014).…”
supporting
confidence: 48%
“…Escherichia coli DnaK/DnaJ or GroEL/GroES systems may additionally mimic specialized cyanobacterial (but not eukaryotic) Rubisco-interacting proteins at pre-assembly Rubisco biogenesis stages. The existence of such particular factors as interacting with RbcL nascent chain Bsd2 (Doron et al 2014) or specialized Cpn60 subunits required for rice RbcL folding (Kim et al 2013) has been confirmed for eukaryotic cells.…”
Section: Discussionmentioning
confidence: 98%
“…It is postulated that to achieve a proper tertiary structure RbcL requires the action of chaperonin (chloroplast Cpn60/Cpn20/Cpn10 or prokaryotic GroEL/GroES; Barraclough and Ellis 1980; Goloubinoff et al 1989). Moreover, before that stage, a specific DnaJ-like factor—Bsd2, found in eukaryotic chloroplasts seems to be crucial during the folding of the N-terminal domain of the large Rubisco subunit (Brutnell et al 1999; Doron et al 2014). To form the octameric core of Rubisco, properly folded RbcLs first need to be dimerized, and to achieve this goal the participation of the so-called assembly chaperones is required.…”
Section: Introductionmentioning
confidence: 99%
“…The function of BSDII in plant chloroplasts is uncertain. BSDII may interact with newly synthesized L-peptides (Doron et al, 2014) or at the post-chaperonin stage for Rubisco subunit assembly (Feiz et al, 2014). See text for further details.…”
Section: Reviewmentioning
confidence: 99%